Role of Nigella sativa in the Management of Osteoarthritis: A Systematic Review - Mozhdeh Ghamari; Masoumeh Salari; Mandana Khodashahi (Tehran University of Medical Sciences, 2023)
Because of the anti-inflammatory properties of thymoquinone (TQ), as the main bioactive substance of Nigella sativa, this systematic review aimed at assessing the therapeutic effects of N. sativa and its main bioactive substance in the management of patients with osteoarthritis (OA) in vivo, in vitro, and in clinical studies. The methodology was adjusted based on the Cochrane Handbook recommendations. All published articles focusing on N. sativa as a therapeutic agent for the treatment of OA or its animal model were searched up to 20 April 2022 in PubMed, Medline, Web of Sciences, and Scopus databases. The search process was carried out using the following keywords: "Nigella sativa", "Black seed', "Black cumin", and "Thymoquinone" in combination with "Osteoarthritis". Finally, 14 articles remained, including five intervention clinical trial, two human in vivo studies, and seven animal studies. Four of five intervention studies showed that N. sativa administration led to relief in pain intensity. In the other clinical trial, no difference was reported between the N. sativa and control groups in terms of pain relief among OA patients. Studies demonstrated the anti-inflammatory and chondroprotective effects of TQ as the main bioactive substance of NS. The evidence confirmed the anti-inflammatory and chondroprotective effects of N. sativa in the management of OA patients. Due to the lack of allergic reaction to N. sativa in the aforementioned studies, this substance can be used as a safe adjuvant treatment to relieve OA pain, compared to nonsteroidal anti-inflammatory drugs and other analgesics.